Clinical significance of Nosocomiicoccus ampullae isolated from blood cultures - Victoria L. Campodónico; Tsigereda Tekle; Yehudit Bergman; Jennifer Lu; Emily Gisriel; Mark Romagnoli; Dimitrios Bourdas; Ann Hanlon; Carmila Manuel; Romney Humphries; Patricia J. Simner; Karen C. Carroll (Microbiology Spectrum, 2023)
ABSTRACT Nosocomiicoccus species are infrequently isolated from clinical specimens and their clinical significance has not been evaluated. We retrospectively reviewed five cases in which Nosocomiicoccus ampullae was identified in a single blood culture set during routine culture. All patients were admitted for altered mental status and had several comorbidities. Patients improved without antibiotic therapy directed to N. ampullae or their condition declined due to underlying conditions, and N. ampullae isolation was not considered clinically significant in any case. Matrix-assisted laser desorption/ionization-time of flight mass spectrometry and/or 16S rRNA gene Sanger sequencing allowed genus identification, but whole genome sequencing was required for accurate species identification. All strains were susceptible to penicillin, oxacillin, cefoxitin, tetracycline, doxycycline, daptomycin, minocycline, clindamycin, nitrofurantoin, vancomycin, and linezolid; they showed high-level resistance to trimethoprim-sulfamethoxazole and erythromycin, and inducible resistance to clindamycin, applying Clinical and Laboratory Standards Institute Staphylococcus spp. guidelines with an extended incubation. They frequently carry genes associated with macrolide resistance. In conclusion, N. ampullae appears to have low pathogenicity and most probably represents a contaminant when isolated from a single blood culture set. IMPORTANCE Nosocomiicoccus species are recently described as members of the Staphylococcaceae family. With their inclusion in commercial matrix-assisted laser desorption/ionization-time of flight mass spectrometry databases, Nosocomiicoccus species can now be identified when Gram-positive cocci in clusters are detected in positive blood cultures. However, their clinical significance is not known, making it difficult for the clinical microbiology laboratory to decide the extent of work-up. Based on our study, Nosocomiicoccus species demonstrate low pathogenicity and opportunistic potential. If isolated from a single blood culture set, limited work-up should be performed to an extent similar to other possible blood culture contaminants.